Bioprospecting of an Endolichenic Fungus Phanerochaete sordida Isolated from Mangrove-Associated Lichen Bactrospora myriadea. (16th April 2022) - Weerasinghe, Ramani H.; Shevkar, Chaitrali D.; Maduranga, Kasun; Pandey, Komal H.; Attanayake, Renuka N.; Kate, Abhijeet S.; Weerakoon, Gothamie; Behera, Santosh K.; Kalia, Kiran S.; Paranagama, Priyani A.
Abstract : Bioassay-guided fractionation of the ethyl acetate extract of Phanerochaete sordida, an endolichenic fungus (ELF) isolated from the host lichen Bactrospora myriadea, collected from Negombo lagoon, Sri Lanka, led to the isolation of a bioactive compound. Following the identification of the fungus using morphological and DNA barcoding techniques, the pure compound was isolated using column chromatography, preparative TLC, and semipreparative HPLC. The structure elucidation was carried out using IR, HR-ESI-MS and 1 H, 13 C & 2D NMR spectroscopic methods. The in vitro bioassays conducted revealed that compound 1 has a high antioxidant activity with ABTS + (IC50 58.91 ± 1.35 μ M ), moderate anti-inflammatory activity (IC50 254.79 ± 1.41 μ M ), comparable antibacterial activity against the oral-bacterial strain Streptococcus mutans (MIC 898.79 μ M and MLC 1797.58 μ M), moderate tyrosinase inhibition (IC50 1713.69 ± 8.65 μ M ), and moderate cytotoxicity against oral cancer (IC50 13.65 ± 0.02 μ M ), in comparison with respective positive controls. The in silico experiments conducted for tyrosinase inhibition and cytotoxicity using Schrödinger revealed results in line with the in vitro results, thus confirming the bioactivities. The molecule also satisfies the key features of drug likeliness according to pharmacokinetic studies.